Novel Temporal Expression Patterns of EBF-Binding Proteins in Wing Morphs of The Grain Aphid Sitobion miscanthi - Zhang, Siyu; Zhang, Qian; Jiang, Xin; Li, Qian; Qin, Yaoguo; Wang, Wenkai; Fan, Jia; Chen, Julian (Frontiers in Physiology, 2021)
High chemosensitivity of insects to volatile organic compounds (VOC) stimuli is mediated by odorant binding proteins (OBPs). In aphids, three OBPs (OBP3, OBP7 and OBP9) are E-β-farnesene (EBF)-binding proteins. Winged aphids are generally more sensitive than wingless aphids to VOCs, thus, wing presence is a phenotypic correlate of olfaction sensitivity. Here, we investigate the detailed temporal expression of these EBF-binding proteins and two other OBPs (OBP6 and OBP10), in the grain aphid Sitobion miscanthi 0 h, 2 h, 1 d, 3 d, 10 d and 20 d after adult emergence. Both winged and wingless aphids were examined to further uncover phenotypic specification. Then, the expression patterns before and after EBF induction were analyzed. Throughout adulthood, only OBP7 had significantly higher antennal expression in winged aphids; however, there was no significant difference in the antennal expression of OBP3 between wing morphs at most time points. Except it was lower in newly emerged winged aphids but increased rapidly to the same level in wingless aphids at 1 d. OBP9 did not differ in expression between the morphs and was the only OBP that did not exhibit an expression trough at the beginning of the adult stage (0 h). The expression of OBP9 remained relatively stable and high throughout the adult stage in both phenotypes, showing the highest level among the three EBF-binding proteins. After EBF induction, its expression was further up-regulated in both morphs. Therefore, this protein may be an important molecule for EBF recognition in aphids. OBP7 strongly responded to EBF but only in winged aphids, suggesting that this protein is important in the more sensitive EBF recognition process of winged aphids. In addition, the antennal expression level of OBP3 did not respond to EBF induction. These findings revealed a temporal expression pattern of OBPs in aphids and showed that figuring out the pattern is critical for correctly selecting morphs and sampling times, which will support the discovery of reliable findings and allow solid conclusions to be drawn. Our findings also inspire on the interaction mode of the three EBF-binding proteins in relation to EBF perception in aphids.